The Impact of Colorectal Cancer Screening in a Veteran Hospital Population. Issue 3 (March 2013) - Trombold, John; Farmer, Russellw; McCafferty, Michael
Colon and rectal cancer is the second most common cause of cancer death in the United States. Screening effectively decreases colorectal cancer mortality. This study aims to evaluate the impact of colorectal cancer screening within a Veterans Affairs Medical Center and treatment outcomes. Institutional Review Board approval was obtained for a retrospective analysis of all colorectal cancer cases that were identified through the Tumor Registry of the Robley Rex VA Medical Center from 2000 to 2009. Data collected included age at diagnosis, race, risk factors, diagnosis by screening versus symptomatic evaluation, screening test, tumor location and stage, operation performed, operative mortality, and survival. A value of P < 0.05 on Fisher's exact, χ 2, analysis of variance, or Cox regression analyses was considered significant. Three hundred fifty-four patients with colorectal cancer (255 colon, 99 rectal) were identified. One hundred twenty-one patients (34%) were diagnosed by screening. In comparison with those diagnosed by symptom evaluation (n = 233), these patients had earlier stage cancers, were more likely to have a curative intent procedure, and had improved 5-year survival rates. Older patients (older than 75 years old) were more likely to present with symptoms. High-risk patients were more likely to have colonoscopic screening than fecal occult blood testing. More blacks had Stage IV disease than nonblacks. Curative intent 30-day operative mortality was 2.1 per cent for colectomy and 0 per cent for rectal resection. Screening for colorectal cancer in the veteran population allows for better survival, detection at an earlier stage, and higher likelihood of resection.